Spectrum of ovarian lesions in all age groups in a tertiary care hospital in Karachi Pakistan: a 5 year study - Ahmed, Naseem; Abbas, Syeda Hina; Azim , Umme Aiman; Afzal , Maryyam Tehreem; Mahboob, Aiman; Ansari, Arsh-e-Mah (International Journal of Pathology, 2025)
Background:  Ovaries are a site of wide range of pathologies consisting of both malignant and benign lesions. They are a source of immense morbidity and mortality for females .Ovarian lesions tend to vary depending on age with malignant ones being more common in older age and benign being prevalent in younger patients. Ovarian cancers pose a great challenge because of their late detection, the reason being their asymptomatic nature or very vague symptoms. The aim of our study is to find out the prevalence of these wide array of lesions in different age group among cases presented in Civil hospital Karachi from 2019 to 2023.Methods: This is a retrospective cross-sectional study of ovarian specimens received at pathology department of Dow Medical College Karachi from Civil Hospital Karachi in five year duration from 2019 to 2023.Specimens were obtained from unilateral or bilateral salpingo-oopherectomy with or without hysterectomy. Data regarding age, clinical suspicion, histological diagnosis and menopausal status was entered and analyzed using SPSS version 25.Results: From 2019-2023, out of 548 ovarian lesions, 312 (56.9%) were neoplastic while 236 (43.1%) were non neoplastic. The most common non neoplastic lesions were endometriotic cyst (30.93%). Neoplastic lesions occurred mainly in age group 16-30. Among them majority were benign cases. Dermoid cyst (29.16%) was most frequent benign tumor while serous papillary carcinoma (8.33%) was the most common malignancy.Conclusion: Neoplastic lesions were more common than non-neoplastic ones, with benign dermoid cysts being the most common. Young individuals were primarily affected.